Summary of environmental effect and seismic activity in Qinghai-Xizang Plateau - Yanyun Zhang; Yu Zhang; Huazheng Su; Ruidong Li; Bingbing Han (Earthquake Research Advances)
This paper focuses on the Qinghai-Xizang Plateau. It systematically reviews its seismic activity characteristics and extensive environmental effects under extreme climatic conditions in dry and cold seasons. Firstly, through detailed data analysis and literature review, it is revealed how the seasonal significant rainfall and temperature changes in the plateau establish potential links with key parameters such as the frequency and intensity of seismic activity. This process deeply analyzes how natural conditions such as extreme rainfall and temperature changes directly or indirectly affect the mechanism of earthquake preparation and triggering, which may promote or inhibit the occurrence of seismic activity. The close relationship between cold and dry seasons and seismic activity is emphasized, and the unique influence of these special climatic conditions on seismic activity patterns is discussed. In addition, the regional distribution characteristics of seismic activity in the plateau area are also analyzed, including key data such as annual occurrence number and magnitude distribution, which provides strong data support for formulating regional earthquake disaster response strategies. In addition, the characteristics of various secondary disasters that may be caused by earthquakes, such as landslides, debris flows, barrier lakes, etc., are analyzed, which deepens the understanding of the complexity of the earthquake disaster chain. The aim is to provide a scientific basis for future earthquake disaster prevention and control work and to promote the improvement of earthquake science research and disaster management levels in the Qingzang Plateau and even the world.